2012
DOI: 10.5005/jp-journals-10012-1067
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Efficacy of Calcium Sulfate Bone Grafts in Crystalline and Nano-Crystalline Forms in Fresh Extraction Socket Sites: A Radiographic and Histological Pilot Study

Abstract: Aim: Extraction site reconstruction is essential for alveolar ridge preservation, keeping in mind future placement of implants. In an attempt to preserve the alveolar bone and to avoid ridge augmentation prior to implant placement, numerous biocompatible regenerative materials have been used immediately following tooth extraction to fill the socket.Methodology: This article is a pilot trial presenting early trends of the comparative use of two forms of calcium sulfate, i.e. medical grade (Dentogen) ® and nano-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 82 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…A large amount of proteins on n-HA films compared to hydroxyapatite particle films were found by Zhou et al [39]. Furthermore, Jain and co-workers [40] indicated that degradation of calcium sulphate particles which decreases local pH can result in demineralization of defects walls and release of growth factors, such as BMP-2, BMP-7, TGF-ß, and PDGF-BB. The results of a study by Pezzatini et al [41] showed that n-HA increased upregulation of FGF-2, and stimulated endothelial cells proliferation.…”
Section: Effects Of N-ha On Growth Factors Releasementioning
confidence: 95%
See 2 more Smart Citations
“…A large amount of proteins on n-HA films compared to hydroxyapatite particle films were found by Zhou et al [39]. Furthermore, Jain and co-workers [40] indicated that degradation of calcium sulphate particles which decreases local pH can result in demineralization of defects walls and release of growth factors, such as BMP-2, BMP-7, TGF-ß, and PDGF-BB. The results of a study by Pezzatini et al [41] showed that n-HA increased upregulation of FGF-2, and stimulated endothelial cells proliferation.…”
Section: Effects Of N-ha On Growth Factors Releasementioning
confidence: 95%
“…Therefore, it is appropriate for post-extraction socket preservation and minimizing the very small amount of remnant graft material around dental implants [42]. The evaluation of the efficacy of two forms of calcium sulphate, crystalline and nanocrystalline, in fresh extraction socket by Jain et al [40] revealed that both materials can be considered as an appropriate regenerative graft material with density compared to the surrounding bone. Canullo et al [43] conducted an assessment of fresh post-extraction sockets grafted with Mg-enriched n-HA.…”
Section: Resorbability Of N-hamentioning
confidence: 99%
See 1 more Smart Citation
“…The results in this study also indicated that CaSO 4 scaffolds fabricated by SLS possessed a good biocompatibility. Compressive strength (MPa) 5 Laser power (W) 6 7 8 …”
Section: Biocompatibilitymentioning
confidence: 99%
“…When CaSO 4 is implanted in vivo, it can degrade and offer the main mineral constituent of bone tissue. So it has long been used to fill bone fractures [5][6][7]. The calcium sulfate demonstrates firmer supporting for bone defect site after solidification than calcium phosphate [8].…”
Section: Introductionmentioning
confidence: 99%